Customer relationship management systems (CRMS) in the healthcare environment: A systematic literature review - Baashar Y.; Alhussian H.; Patel A.; Alkawsi G.; Alzahrani A.I.; Alfarraj O.; Hayder G. (Elsevier B.V., 2023)
Data mining; Hospitals; Industrial research; Knowledge management; Patient treatment; Public relations; Quality control; Sales; Analysis and evaluation; Customer relationship management; Customer relationship management systems; Customer relationships; Healthcare environments; Innovative technology; Medical operations; Systematic literature review; Customer satisfaction